Analisis Rasio Solvabilitas dan Rasio Profitabilitas Untuk Mengukur Kinerja Keuangan Pada Toko Karpet Win Jaya Sibolga Periode 2020-2024 - Elfrida Amelia Nasution; Zafril Abdi Nasution; Andrian Irsyan (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the financial performance of Toko Karpet Win Jaya Sibolga using solvency and profitability ratios during the 2020–2024 period. The research method employed is a quantitative descriptive approach using financial ratio analysis based on the company’s financial statements. The solvency ratios analyzed include Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Long Term Debt to Equity Ratio (LTDER). The results show that the average DAR is 15.30%, DER is 14.05%, and LTDER is 4.89%, indicating that the company has a healthy capital structure with low dependence on debt and a strong ability to meet its long-term obligations. Meanwhile, the profitability ratio analysis reveals that the company’s net income fluctuated during the study period, increasing in 2021, declining in 2022–2023, and rising again in 2024. Overall, the company’s financial performance is considered good; however, improvements are needed to maintain profitability stability through cost efficiency and optimal asset utilization.